2019
DOI: 10.1177/1533033819875168
|View full text |Cite
|
Sign up to set email alerts
|

miR-206 Promotes Cancer Progression by Targeting Full-Length Neurokinin-1 Receptor in Breast Cancer

Abstract: Substance P plays a pivotal role in human cancer development and progression by binding to its receptor, neurokinin-1. Neurokinin-1 has 2 isoforms: full-length neurokinin-1 and truncated neurokinin-1, the latter lacking the cytoplasmic terminal 96-amino acid residues of the full-length protein. We have identified 3 candidate miR-206 target sites within the 3′-untranslated region of the full-length neurokinin-1 gene from bioinformatics database searches. In the present study, real-time quantitative polymerase c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 39 publications
1
35
0
Order By: Relevance
“…The role of miR-206 in cancers is complicated and controversial. Decreased expression of miR-206 was found in rhabdomyosarcoma [ 26 ], lung cancer [ 28 ], ER + breast cancer [ 29 , 30 ], renal cell carcinoma [ 31 ], ER alpha + endometrioid adenocarcinoma [ 32 ], hepatocellular carcinoma [ 33 , 34 ] and glioma [ 35 ]. Upregulation of miR-206 inhibits the migration, invasion and proliferation of breast cancer [ 30 ], renal cell carcinoma [ 31 ], glioma [ 35 ], and head and neck squamous cell carcinoma [ 31 ], suggesting a tumor suppressor role of miR-206.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The role of miR-206 in cancers is complicated and controversial. Decreased expression of miR-206 was found in rhabdomyosarcoma [ 26 ], lung cancer [ 28 ], ER + breast cancer [ 29 , 30 ], renal cell carcinoma [ 31 ], ER alpha + endometrioid adenocarcinoma [ 32 ], hepatocellular carcinoma [ 33 , 34 ] and glioma [ 35 ]. Upregulation of miR-206 inhibits the migration, invasion and proliferation of breast cancer [ 30 ], renal cell carcinoma [ 31 ], glioma [ 35 ], and head and neck squamous cell carcinoma [ 31 ], suggesting a tumor suppressor role of miR-206.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased expression of miR-206 was found in rhabdomyosarcoma [ 26 ], lung cancer [ 28 ], ER + breast cancer [ 29 , 30 ], renal cell carcinoma [ 31 ], ER alpha + endometrioid adenocarcinoma [ 32 ], hepatocellular carcinoma [ 33 , 34 ] and glioma [ 35 ]. Upregulation of miR-206 inhibits the migration, invasion and proliferation of breast cancer [ 30 ], renal cell carcinoma [ 31 ], glioma [ 35 ], and head and neck squamous cell carcinoma [ 31 ], suggesting a tumor suppressor role of miR-206. Increased expression of miR-206 was found in breast cancer [ 30 , 36 ], esophageal carcinoma [ 37 ] and some soft tissue sarcomas [ 38 ], and high miR-206 expression was related to the poor prognosis of breast cancer [ 36 ] and esophageal carcinoma patients [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lymph node involvement and the cancer stage have been related to the expression of the NK-1R and, in fact, patients with poor prognosis and more advanced and less-differentiated tumors expressed a higher number of NK-1Rs [30,31,35]. This is an important observation, because it means that the NK-1R can be used in cancer as a biomarker and it could be useful for an earlier diagnosis/treatment of the disease [30].…”
Section: The Sp/nk-1r System As a Predictive Factor In Cancer And Thementioning
confidence: 99%
“…Regarding the expression of the NK-1R, the study showed that two isoforms of the NK-1R (full-length and truncated) were present in AML cells and, in particular, the truncated form was two-fold higher than the full-length isoform ( Table 1) [23]. In cancer cells, the truncated isoform is up-regulated and the full-length form downregulated and it has been suggested that a low level of the full-length isoform is responsible for the malignant phenotype of cancer cells [35]. However, in healthy cells, the truncated isoform was not expressed, whereas the full-length isoform was higher in AML cells (20-fold in KG-1 and 12-fold in HL-60) when compared to healthy cells (Table 1) [23].…”
Section: Aprepitant Did Not Exert a Proliferation-inhibitory Effect Amentioning
confidence: 99%